2014
DOI: 10.4236/fns.2014.52027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Functional Properties between Native and Chemically Modified Starches from Acha (<i>Digitaria</i> Stapf) Grains

Abstract: Acha grain (Digitariaexilis) starch was isolated and subjected to chemical modifications by acetylation, benzylation, succinylation, carboxymethylation and acid-thining. Functional properties (swelling, solubility, gelation, oil and water absorption capacities, alkaline water retention) and rheological properties of the native and modified starches were determined. Swelling power and solubility of the starch samples increased with increase in temperature. Swelling power and solubility were pH dependent, with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…Emeje et al, 2012 observed that Acetylated acha starch had better functional properties than the Native starch. Olu-Owolabi, Olayinka, Adegbemile, and Adebowale (2014) endeavored to compare the functional properties of Native acha starch with its chemically modified forms. He concluded amongst other findings that chemical modification increased pasting temperature and reduced setback values.…”
Section: Introductionmentioning
confidence: 99%
“…Emeje et al, 2012 observed that Acetylated acha starch had better functional properties than the Native starch. Olu-Owolabi, Olayinka, Adegbemile, and Adebowale (2014) endeavored to compare the functional properties of Native acha starch with its chemically modified forms. He concluded amongst other findings that chemical modification increased pasting temperature and reduced setback values.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in pasting temperature elucidated that the pretreatment of black rice pasta increases the crystalline region due to the reorientation of starch granules. As the crystallinity increases the potency of bonding between the molecules which makes more heat involvement in paste formation (Olu‐Owolabi, Olayinka, Adegbemile, & Adebowale, ). The peak, hold, and final viscosity of untreated pasta were 2,452, 1,635, and 2,979 cP, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The esterification process was carried out as described by Lawal () and Olu‐Owolabi, Olayinka, Adegbemile, and Adebowale () with some modifications. The native starch (150 g) was suspended in 500 mL of distilled water and magnetically stirred for 20 min.…”
Section: Methodsmentioning
confidence: 99%